Study of rainfall-runoff relationship using hydrological modelling system (HEC-HMS) for Kurau river Basin, Perak - Amanina, Nasruddin (2014)
Landuse changes and urbanisation has always been blamed as among the major causes of the increase in the magnitude and frequency flooding. Flash flood had occured in Kurau River due to low lying of the draining area which the drainage capacity cannot cattle the quantity of water when the capacity of runoff increases. When the quantity of the runoff is increasing and filled all the drainage and river, the flood will then occur. Therefore, this research aim is to to carry out rainfall-runoff modelling exercises using HEC-HMS Model, determine the rainfall-runoff relationship in Kurau River basin, Perak and to get appropriate model to predict discharge after calibration, validation and verification process. Relationship between rainfall and runoff will then be determined by the producing hydrograph from this software. In this software, hydrology parameter such as rainfall data and stream flow data are important to simulate rainfall-runoff data. In this study, HEC-HMS were used to develop hydrologic model for Sungai Kurau Basin based on the available data. These models were calibrated on November 1999 and validate on March 1999. The simulated model were approximately fit with the observed data and shows that the HEC-HMS are suitable model to predict hydrologic changes in Sungai Kurau Basin. The performance of determination RMSE value is used to measure the performance of the hydrologic modelling. From the calibration results, the RMSE value for Bt 14 discharge station and Pondok Tanjung were 2.060 m3/s and 1.474 m3/s. From the validation result, the RMSE value for Bt 14 discharge station and Pondok Tanjung were 1.342 m3/s and 1.846 m3/s. Lower values are better.